Rosyjski Kościół Prawosławny wobec zbrojnej agresji na Ukrainę. Narracja wojenna w kazaniach patriarchy Cyryla I - Kondzioła-Pich, Katarzyna (Slavia Orientalis, 2025)
The aim of the article is to examine the sermons of the patriarch of the Russian Orthodox Church, Kirill I, in order to find elements that might be regarded as examples of war propaganda. The analysis was based on sermons Kirill I gave during the first two years of the Russian-Ukrainian war (2022-2024). As a result of the examination some mission statements in the patriarch’s utterances were discovered, among which the idea of the ethnical identity of East Slavic nations and the necessity to unify them may be treated as one of the most crucial. The main purpose of Kirill I’s statements is to trigger emotions in his listeners and make them change their attitude to the war and to Ukraine and Ukrainians according to the expectations of the Russian authorities. The vocabulary and the persuasive strategies Kirill has employed in his sermons allow us to qualify his statements as a part of Russian war propaganda.